Development of solar powered boats for water quality monitoring - ทีปรักษพันธุ์ สุธิดา; ใจแก้ว ปิยนุช (Srinakharinwirot University Engineering Journal, 2019)
This paper presents the development of a water quality monitoring system using boats powered by renewable energy. To monitor the quality of water by measuring various parameters for a water sample in water resources, a prototype boat using powered by solar cell was designed and implemented. Data collected by various sensors such as pH, temperature, total dissolved solids, and oxygen density was collected in different depth of water. The solar-powered boat’s weight around 8 kg. The average speed on the water surface was 5-10 km/hr. The solar panels on the boat can create electricity as around 54.24 Wh. The principle of maximum work was around 10 hr. Our system has advantages such as low carbon emission, low power consumption, more flexible to deploy.